2017
DOI: 10.3390/safety4010001
|View full text |Cite
|
Sign up to set email alerts
|

Correct Use of Three-Point Seatbelt by Pregnant Occupants

Abstract: Abstract:The largest cause of accidental death and placental abruption in pregnancy is automobile collisions. Lives can be saved by correct use of the three-point seatbelt during pregnancy. Human interaction is essential for correct use of seatbelts. The objective of this study is to investigate pregnant women's use of correct shoulder section together with correct lap section as advised by obstetricians and highway experts and to identify the most common seatbelt misuse during pregnancy. An international web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, a substantial number of pregnant women are not willing to wear three-point seatbelts because of a compressive feeling or discomfort. Acar et al suggested that the rate of seatbelt use during pregnancy in Europe, North America, and other countries was 94.8%, 92.2%, and 83.3%, respectively [ 9 ]. In Malaysia, 57.6% of pregnant drivers always used a seatbelt [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a substantial number of pregnant women are not willing to wear three-point seatbelts because of a compressive feeling or discomfort. Acar et al suggested that the rate of seatbelt use during pregnancy in Europe, North America, and other countries was 94.8%, 92.2%, and 83.3%, respectively [ 9 ]. In Malaysia, 57.6% of pregnant drivers always used a seatbelt [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The seatbelts should be properly placed. The lap section should be under the bump and across the hips, while the shoulder section should pass between the two breasts and around the abdomen [ 32 ].…”
Section: Discussionmentioning
confidence: 99%